Adaptasi Skala PTGI (Posttraumatic Growth Inventory) Pada Orang Tua Anak Pengidap Kanker Leukemia - Abdillah, Andi Arif; Ridfah, Ahmad; Wahyuni, Andi Fitri (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
Parents of children with leukemia often face traumatic experiences that significantly affect their psychological well-being; however, these experiences may also lead to positive psychological changes known as posttraumatic growth. Measuring posttraumatic growth requires a valid and reliable instrument that is appropriate to the cultural context and population characteristics. This study aimed to adapt and examine the psychometric properties of the Posttraumatic Growth Inventory (PTGI) for parents of children with leukemia in Indonesia. A quantitative psychometric approach was employed, involving 121 parents as participants. Data analysis included content validity testing through expert judgment, item discrimination analysis, factorial validity using Confirmatory Factor Analysis (CFA), reliability testing, and score norming. The results of content validity analysis indicated Aiken’s V coefficients ranging from 0.80 to 0.90. From the initial 21 items, 16 items met the criteria for item discrimination and factorial validity, forming five PTGI dimensions. Reliability analysis demonstrated high internal consistency, with Cronbach’s Alpha of 0.915 and McDonald’s Omega of 0.917. Norming procedures yielded five levels of posttraumatic growth. These findings indicate that the adapted PTGI is valid, reliable, and suitable for assessing posttraumatic growth among parents of children with leukemia in Indonesia.